Characidium serrano Buckup & Reis, 1997 (Characiformes, Crenuchidae): insights into phylogenetic relationships, and comments on distribution - Wilson Serra; Fabrizio Scarabino; Ezequiel Méttola; Martín Miguel Montes; Guillermo Terán; Melisa Moncada; Germán Sanguinetti; Alejandro Duarte; Matías García (Acta Zoológica Lilloana)
Characidium is the most diverse genus within the family Crenuchidae, with a total of 88 valid species, although there is evidence that it is probably a polyphyletic group. Recent expeditions to northern Uruguay revealed the first records of Characidium serrano Buckup & Reis, 1997, extending its distribution in about 300 km to the south and allowing to consider it as an endangered species for Uruguay, considering its restricted distribution in the country. Different phylogenetic reconstructions and comparisons based on COI (Model-based analysis, Parsimony analysis and Evolutionary Divergence between sequences) of new se quences with those previously published indicate: 1) a closer phylogenetic relationship of C. serrano with C. clistenesi or alternatively with (C. rachovii + C. orientale) than with C. pterostictum and 2) non-coincident topologies that in all cases suggest the non-monophyly of Characidium. The analyzed sequences of the genus Characidium formed 9 main stables groups that are obtained in each of the analyzes carried out, which were also recovered in studies previously performed by other authors, but with general topologies not coincident and poorly supported in their basal nodes.